Preventing alcohol‑related problems in the light of the Act of 26 October 1982 on proceedings in juvenile cases Selected issues - Badziak, Justyna (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
Alcohol abuse results in a million deaths every year, a signiﬁcant proportion of which are young people. Moreover, a wide variety of alcohol-related problems can have a devastating impact not only on minors but also on their families, and can seriously affect community life. The occurrence of problems associated with alcohol abuse contributed to a number of strategies aimed at their prevention or partial reduction. The purpose of the article is to present selected actions taken in this scope by juvenile courts, based on the Act of 26th October 1982 on proceedings in juvenile cases. The fact that the Polish system of dealing with young offenders is based on the care-education-protection system, and that the young people’s best interests are recognized as its leading directive, means abandoning repression as the primary measure used against juveniles, and referring to the principle of children’s welfare. This priority of the welfare of juveniles, which has been recognized as a fundamental directive of the Polish model of dealing with them, should theoretically impact all legal solutions adopted within the directive and the decisions taken at every stage. Those that would not prove favourable to the welfare of juveniles (which is defined as the intention to achieve such beneficial changes in his or her personality and behavior so that he or she could properly function in the social reality, in accordance with his or her biological age and maturity) are fundamentally wrong and should be changed or repealed. This also refers to special legal measures, which are supposed to prevent alcohol addiction among minors.